2019
DOI: 10.1016/j.scitotenv.2019.01.144
|View full text |Cite
|
Sign up to set email alerts
|

Impact of CO2 concentration and ambient conditions on microalgal growth and nutrient removal from wastewater by a photobioreactor

Abstract: The increase in atmospheric CO 2 concentration and the release of nutrients from wastewater treatment plants (WWTPs) are environmental issues linked to several impacts on ecosystems. Numerous technologies have been employed to resolves these issues, nonetheless, the cost and sustainability are still a concern. Recently, the use of microalgae appears as a cost-effective and sustainable solution because they can effectively uptake CO 2 and nutrients resulting in biomass production that can be processed into valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 116 publications
(40 citation statements)
references
References 70 publications
(95 reference statements)
1
34
0
Order By: Relevance
“…The concentration of DIC in the culture medium can be increased by continuous or intermittent CO 2 aeration, as has been demonstrated in many studies (Matsudo et al, 2012;Chen et al, 2016;Duarte et al, 2017;Qiu et al, 2017;Almomani et al, 2019). Bao et al (2012) indicated that CO 2 absorptivity has a positive correlation with pH value and a negative correlation with total carbon concentration.…”
Section: Dic Optimizationmentioning
confidence: 69%
See 1 more Smart Citation
“…The concentration of DIC in the culture medium can be increased by continuous or intermittent CO 2 aeration, as has been demonstrated in many studies (Matsudo et al, 2012;Chen et al, 2016;Duarte et al, 2017;Qiu et al, 2017;Almomani et al, 2019). Bao et al (2012) indicated that CO 2 absorptivity has a positive correlation with pH value and a negative correlation with total carbon concentration.…”
Section: Dic Optimizationmentioning
confidence: 69%
“…To improve the CO 2 fixation rate, excellent algal strains need to be selected. Almomani et al (2019) reported that mixed indigenous microalgae (MIMA, collected from a secondary basin of Doha South wastewater treatment plant) performed significantly better than a single Spirulina platensis (SP.PL) culture, especially with respect to growth and CO 2 biofixation (Almomani et al, 2019). Badger and Price (1994) indicated that high CO 2 levels could improve carbon fixation activity of the enzyme rubisco in microalgal cells, and rubisco facilitates the utilization of CO 2 , thus, increasing the biological fixation efficiency of CO 2 .…”
Section: Strain Selectionmentioning
confidence: 99%
“…Carbon dioxide (CO2) fixation methods are well known, and include its conversion to chemical feedstock and fuels, biological conversion (photosynthesis) (Al Momani et al, 2004), and mineralisation for the production of metal carbonate/bicarbonates (Almomani et al, 2019a;Almomani et al, 2019b;Laumb et al, 2013). Whereas these methods mainly focus on CO2 utilisation following capture, biological conversion directly mitigates CO2 and uses it as a feedstock to create useful products.…”
Section: Introductionmentioning
confidence: 99%
“…Microalgae are acknowledged as providing an efficient means of mitigating carbon while generating products such as biofuels (Almomani et al, 2019a;Meher et al, 2006;Mutanda et al, 2011); interest in microalgae culture technology (MCT) has grown significantly since first it was pioneered in the late 1970s (Leduy and Therien, 1979). Algae can utilise both CO2 and organic carbon as the substrate, by autotrophic and mixotrophic growth respectively, such that the technology can potentially be employed for combined CO2 sequestration from flue gases and nutrient removal from wastewater (Almomani et al, 2017;AlMomani and Örmeci, 2016;Shurair et al, 2016;Almomani et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Several processes nowadays that can be used for the treatment of pulp and paper industry wastewater such as biological processes, adsorption, advanced oxidation, chemical coagulation, electrocoagulation, and membrane separation. [31][32][33][34] Cellulose content is the only consideration for the evaluation of a biomass source. This is because the extraction of sugars must practically take place under milder conditions than strong-acid hydrolysis at high temperature.…”
mentioning
confidence: 99%